The therapeutic potential of ayahuasca in depression, generalized anxiety, and substance use disorders: modulation of the depressive burden in a longitudinal study - Camargos, Gláucio Silva; de Faria Júnior, Geraldo Magela; Lourenço, Marcelo; de Araújo Filho, Gerardo Maria (Frontiers in Psychiatry, 2026)
IntroductionThis longitudinal observational study evaluated changes in depressive symptoms associated with ritualistic ayahuasca use in patients diagnosed with depressive disorders, as well as depressive burden in individuals with anxiety and substance use disorders.MethodsThe research was conducted with 280 adults treated at clinics in the northwestern region of the state of São Paulo, under the jurisdiction of Regional Health Division XV (DRS XV), which covers a population of over 2 million inhabitants. Participants were assessed at six different time points over a six-month follow-up period after the ayahuasca intervention, with depressive symptoms measured using the Montgomery–Åsberg Depression Rating Scale (MADRS).ResultsThe results indicate a significant reduction in depression scores shortly after the intervention, with improvements sustained for up to 180 days, though individual responses varied. The analysis reveals that ayahuasca, when combined with psychotherapeutic support, can provide significant benefits in reducing symptoms of depression and anxiety, and also shows potential in the treatment of substance dependence.ConclusionWe concluded that the final variability in responses suggests that psychodynamic and clinical factors, such as the integration of the psychedelic experience and therapeutic support, play a crucial role in treatment effectiveness. This study contributes to the consolidation of psychedelic-assisted therapeutic protocols, highlighting the importance of continuous and personalized follow-up in the treatment of complex psychiatric conditions.